A fast method for psychophysical estimation of nonlinear cochlear processing using Schroeder phase harmonic complexes - Rahmat, Sarah (2014)
Schroeder phase harmonic complexes (Schroeder, 1970) have been used in many psychophysical experiments to examine the phase curvature of cochlear filtering and cochlear nonlinearity. The difference in masked thresholds at different phases of the masker (the "phase effect") is reduced when the cochlea behaves more linearly, e.g. at very high and low stimulus levels and in ears with sensorineural hearing loss (Summers & Leek, 1998). Schroeder phase masking functions have been shown to be more sensitive than pure-tone audiometry in evaluating changes in nonlinear cochlear function as a result of cochlear implant surgery (Gifford et al., 2008). Previous studies have typically used three-alternative forced-choice (3 AFC) techniques to measure Schroeder phase masking functions, taking around 45 minutes per curve. We have developed a fast method of measuring the same function in 8 minutes using a Békésy tracking procedure. We aimed to determine whether our new technique produced results equivalent with the conventional 3AFC technique, to establish its test-retest reliability, and to use it to measure Schroeder phase masking functions in normal hearing and hearing impaired participants.